2018
DOI: 10.4236/oalib.1104526
|View full text |Cite
|
Sign up to set email alerts
|

Multitemporal Analysis of Coastal Erosion Based on Multisource Satellite Images in the South of the Mono Transboundary Biosphere Reserve in Togo (West Africa)

Abstract: Climate change is affecting terrestrial and maritime ecosystems of Mono transboundary biosphere reserve and the whole Togolese coast. This research focuses both on the dynamics of the barrier beach and on spatial and temporal changes that affected the ocean coastline and its adjacent Lake Togo and Lake Boko during the period 1988-2018. The methodological approach adopted is based on a combination of optical and radar remote sensing. As results, the Lake Togo widened on average by 1.55 m/year while the coastlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 4 publications
(4 reference statements)
3
19
0
1
Order By: Relevance
“…The manifestations of these factors are more and more felt with the everincreasing population of the area, thus increasing resource needs and accentuating pressure on land (Adjonou et al, 2013). Conversions of natural forests into agricultural and non-vegetated areas observed in the RBTM are common and support earlier work on changes in land use (Ouedraogo et al, 2010;Houessou et al, 2013;Brandt et al, 2014;Faye et Cheikh, 2016;Konko et al, 2018a). This trend in reduced natural vegetation cover in West Africa is an urgent environmental concern as it leads to soil and ecosystem degradation (Avajoudjo et al, 2014;Faye et Cheikh, 2016;Zoungrana et al, 2018).…”
Section: Discussionsupporting
confidence: 79%
“…The manifestations of these factors are more and more felt with the everincreasing population of the area, thus increasing resource needs and accentuating pressure on land (Adjonou et al, 2013). Conversions of natural forests into agricultural and non-vegetated areas observed in the RBTM are common and support earlier work on changes in land use (Ouedraogo et al, 2010;Houessou et al, 2013;Brandt et al, 2014;Faye et Cheikh, 2016;Konko et al, 2018a). This trend in reduced natural vegetation cover in West Africa is an urgent environmental concern as it leads to soil and ecosystem degradation (Avajoudjo et al, 2014;Faye et Cheikh, 2016;Zoungrana et al, 2018).…”
Section: Discussionsupporting
confidence: 79%
“…However, it is important to note that the MSI sensor rendered scenes better than the TM and ETM+ sensors [18].…”
Section: Discussionmentioning
confidence: 99%
“…SVM is a statistical learning classification technique. SVM focuses classification decisions on the boundary between classes instead of their mean and variance values[18].…”
mentioning
confidence: 99%
“…Climate change and its effects are of global concern and has become an active area of research for scientists [1]. One of the consequences of climate change is global warming causing melting glaciers, rising sea levels and shoreline regression [2]. A shoreline is the line of contact between land and a sea [3].…”
Section: Introductionmentioning
confidence: 99%
“…Due to its configuration, the Togolese coast faces many challenges such as urban expansion and coastal erosion. The recent research of [2] in the East of the Togo coast showed that, the shoreline experienced an average recession ranging from 1.66 to 5.25 m per year while the urban area increases from 7.84 ha per year. Predictions based on those averages rate showed that the barrier beach with its residential areas whose the local population estimated at 82.724 inhabitants are exposed to a continual risk of inundation by shoreline regression which may affect more than 7% of its surface area by the 2070s.…”
Section: Introductionmentioning
confidence: 99%